2013
DOI: 10.1016/j.bbamem.2012.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucosylceramide on the biophysical properties of fluid membranes

Abstract: Glucosylceramide (GlcCer), a relevant intermediate in the pathways of glycosphingolipid metabolism, plays key roles in the regulation of cell physiology. The molecular mechanisms by which GlcCer regulates cellular processes are unknown, but might involve changes in membrane biophysical properties and formation of lipid domains. In the present study, fluorescence spectroscopy, confocal microscopy and surface pressure-area (π-A) measurements were used to characterize the effect of GlcCer on the biophysical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
29
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 77 publications
12
29
2
Order By: Relevance
“…This response could be a consequence of the increased tilt in the extracellular domain in the absence of GluCer but could also indicate that GluCer has a stabilizing effect on the transmembrane helices through modification of the membrane properties. In agreement with previous findings 31 , we showed that the presence of GluCer in the membrane increased the lipid order and therefore lipid packing, which could contribute to the stability of the helices and thereby to a reduction in the LPS-induced tilt of the TLR4 extracellular domain. Patra et al .…”
Section: Discussionsupporting
confidence: 93%
“…This response could be a consequence of the increased tilt in the extracellular domain in the absence of GluCer but could also indicate that GluCer has a stabilizing effect on the transmembrane helices through modification of the membrane properties. In agreement with previous findings 31 , we showed that the presence of GluCer in the membrane increased the lipid order and therefore lipid packing, which could contribute to the stability of the helices and thereby to a reduction in the LPS-induced tilt of the TLR4 extracellular domain. Patra et al .…”
Section: Discussionsupporting
confidence: 93%
“…Using TLC, separate groups concluded that glycolipids might be involved in binding to tear lipocalins ( 18 ). It has been suggested that the lacrimal gland might be a probable source of such lipids and that the protein lipocalin might be secreted from the gland already fully charged with these lipids ( 20 ). Correspondingly, our results showed that GluCer is hydroperoxides ( 15 ).…”
Section: Study Groupsupporting
confidence: 72%
“…Receptor dimerization is affected by membrane lipid composition [35]. In GD, changes in lipid composition affect a number of biophysical properties of membranes [36], and we suggest that altered GlcCer levels may directly impinge upon, and perhaps stimulate PRR dimerization, thus activating the IFN response. Nevertheless, since this response can be eliminated with no effect on the lifespan, at least in nGD mice, activation of the IFN pathway may be unrelated to primary disease pathophysiology.…”
Section: Discussionmentioning
confidence: 87%